Association between speech perception in noise and electrophysiological measures: an exploratory study of possible techniques to evaluate cochlear synaptopathy in humans. (2nd June 2020) - Megarbane, Lynn; Fuente, Adrian
Abstract: Objective: The primary aim of this study was to investigate whether scores for a speech-in-noise test were associated with the results of two electrophysiological techniques mainly targeting low spontaneous rate, high-threshold auditory fibres. Design: Cross-sectional study. Participants were evaluated with the hearing-in-noise test (HINT), along with the Auditory Brainstem Response (ABR) with and without ipsilateral noise. The wave V/I amplitude ratio for the ABR without ipsilateral noise and ABR wave V latency shift in the presence of ipsilateral noise were obtained. Study sample: Twenty adults aged between 20 and 34 years (10 females) who did not report occupational exposure to noise were selected. All participants presented with normal hearing thresholds (0.250–8 kHz) and the presence of distortion product otoacoustic emissions, bilaterally. Results: A significant association between the wave V/I amplitude ratio for the left ear and the HINT scores for the left ear was found. Conclusions: Based on the results of this study, in normal-hearing listeners, the wave V/I ratio is associated with speech-in-noise performance, specifically in the left ear. This non-invasive procedure has the potential to be used in clinical populations who present with speech-in-noise difficulties despite having normal audiograms.